Medical Imaging 2020: Computer-Aided Diagnosis 2020
DOI: 10.1117/12.2551220
|View full text |Cite
|
Sign up to set email alerts
|

EDICNet: An end-to-end detection and interpretable malignancy classification network for pulmonary nodules in computed tomography

Abstract: We present an interpretable end-to-end computer-aided detection and diagnosis tool for pulmonary nodules on computed tomography (CT) using deep learning-based methods. The proposed network consists of a nodule detector and a nodule malignancy classifier. We used RetinaNet to train a nodule detector using 7,607 slices containing 4,234 nodule annotations and validated it using 2,323 slices containing 1,454 nodule annotations drawn from the LIDC-IDRI dataset. The average precision for the nodule class in the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…were frequently used to establish transparent systems. There existed two main ways to use human-understandable features in medical imaging: (1) Extracting hand-crafted features, e.g., morphological and radiomic features, from predicted segmentation masks generated by a non-transparent model [70][71][72][73][74][75][76][77][78][79] followed by analysis of those hand-crafted features using a separate classification module; (2) Directly predicting human-understandable features together with the main classification and detection task [80][81][82][83][84] . In these approaches, all tasks usually shared the same network architecture and parameter weights.…”
Section: In: Interpretabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…were frequently used to establish transparent systems. There existed two main ways to use human-understandable features in medical imaging: (1) Extracting hand-crafted features, e.g., morphological and radiomic features, from predicted segmentation masks generated by a non-transparent model [70][71][72][73][74][75][76][77][78][79] followed by analysis of those hand-crafted features using a separate classification module; (2) Directly predicting human-understandable features together with the main classification and detection task [80][81][82][83][84] . In these approaches, all tasks usually shared the same network architecture and parameter weights.…”
Section: In: Interpretabilitymentioning
confidence: 99%
“…Morphological features, e.g., texture, shape and edge features were frequently considered and used to support the transparency of ML systems 70,72,73,75,76,81,83,93 . Biomarkers for specific problems, e.g., end-diastolic volume (EDV) in cardiac MRI 78,79 and mean diameter, consistency, and margin of pulmonary nodules 80 were commonly computed to establish transparency. For problems with a well-established image reporting and diagnosis systems, routinely-used clinical features, e.g., Liver Imaging Reporting and Data System (LI-RADS) features for Hepatocellular carcinoma (HCC) classification 84 or BI-RADS for breast mass 82 suggested that the ML systems may be intuitively interpretable to experts that are already familiar with these guidelines.…”
Section: Pr: Priorsmentioning
confidence: 99%
“…Although CADe attains a high-metric evaluation, only a few studies have verified the effectiveness of clinical practice by evaluating and comparing the performance of radiologists (Cui et al 2020, Lin et al 2020.…”
Section: Lack Of Clinical Evaluation and Applicationmentioning
confidence: 99%
“…were frequently used to establish transparent systems. There existed two main ways to use human-understandable features in medical imaging: 1) Extracting hand-crafted features, e. g., morphological and radiomic features, from predicted segmentation masks generated by a nontransparent model [26,27,33,61,63,47,86,50,78,104] followed by analysis of those hand-crafted features using a separate classification module; 2) Directly predicting human-understandable features together with the main classification and detection task [55,44,45,77,100]. In these approaches, all tasks usually shared the same network architecture and parameter weights.…”
Section: The Use Of An Attention Mechanism Was the Most Commonmentioning
confidence: 99%
“…Morphological features, e. g., texture, shape and edge features were frequently considered and used to support the transparency of ML systems [26,33,52,61,44,47,86,77]. Biomarkers for specific problems, e. g., end-diastolic volume (EDV) in cardiac MRI [78,104] and mean diameter, consistency, and margin of pulmonary nodules [55] were commonly computed to establish transparency. For problems with a well-established image reporting and diagnosis systems, routinely-used clinical features, e. g., Liver Imaging Reporting and Data System (LI-RADS) features for Hepatocellular carcinoma (HCC) classification [100] or BI-RADS for breast mass [45] suggested that the ML systems may be intuitively interpretable to experts that are already familiar with these guidelines.…”
Section: Pr: Priorsmentioning
confidence: 99%